Mercury accumulation in sediments along an eutrophication gradient in Guanabara Bay, southeast Brazil - Machado,Wilson (2008)
The accumulation of Hg was investigated in sediment cores from Guanabara Bay, Rio de Janeiro, Brazil, sampled along an eutrophication gradient, which was reflected in the sediment physical quality and total organic carbon (TOC) distribution. Sediments from the western bay area are strongly affected by inputs of urban and industrial effluents, showing Hg concentrations up to 7500 ng g-1 and Hg inventories up to 786 mg m-2, in contrast with near-background values found in the northwestern bay area (< 65 ng g-1 and 10.6 mg m-2). A shift from a negative to a positive relationship between Hg and TOC occurred in the most eutrophicated estuary, in which an upward increase in the recorded Hg levels was observed. This increase may be attributed to (i) an increasing riverine Hg input and (ii) an impact of eutrophication on the sediment quality, which may enhance the sediment capacity to accumulate organic matter-bound Hg.